2010
DOI: 10.1088/2040-8978/12/11/115505
|View full text |Cite
|
Sign up to set email alerts
|

Line-scanning tomographic optical microscope with isotropic transfer function

Abstract: An imaging method and optical system, referred to as a line-scanning tomographic optical microscope (LSTOM) using a combination of line-scanning technique and CT reconstruction principle, is proposed and studied theoretically and experimentally. In our implementation a narrow focus line is scanned over the sample and the reflected light is measured in a confocal arrangement. One such scan is equivalent to a transverse projection in tomography. Repeating the scanning procedure in several directions, a number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A line-scanning tomographic optical microscope (LSTOM) [1,2] technique solves the anisotropy problem of the line spread function (LSF), emerging in line scanning systems, using a tomographic method and conserving the enhanced resolution provided by the line illumination.…”
Section: Introductionmentioning
confidence: 99%
“…A line-scanning tomographic optical microscope (LSTOM) [1,2] technique solves the anisotropy problem of the line spread function (LSF), emerging in line scanning systems, using a tomographic method and conserving the enhanced resolution provided by the line illumination.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral resolution limit of a scanning microscope can be defined by the FWHM of the line spread function (LSF) or the point spread function of line-scanning or point-scanning imaging systems, respectively. The resulting transfer function of the imaging system can be made isotropic by repeating the scanning from different directions and reconstructing the image using tomographic methods (e.g., in a line-scanning tomographic optical microscope [16,17]). However, the optical transfer function of a conventional LSM system is not isotropic.…”
mentioning
confidence: 99%
“…Applying the abovementioned methods, I could reduce the effect of the synchronous and asynchronous motion error beyond the resolution limit of TOM. [46] 4. I demonstrated that resolution of the line-scanning TOM arrangement in reflection mode exceeds the resolution of a commercially available point-scanning confocal microscope, using the same microscope objective.…”
Section: Methodsmentioning
confidence: 99%
“…Thus the resolution of TOM, even corrected for the wavelength, is 15% better than that of a confocal microscope. [46] 5. My aim was to design an optical element, containing a birefringent plane plate, which is able to create the diffraction limited illumination line and eliminate the effect of the rotational error.…”
Section: Methodsmentioning
confidence: 99%